Complete heart block in Acute Rheumatic fever - Poudel, CM; Gajurel, RM; Barkoti, M; Acharya, SM; Anil, OM (Nepalese Heart Journal, 2013)
Rheumatic fever can cause a variety of cardiac conduction disturbances. First-degree heart block is a common electrocardiographic manifestation of acute rheumatic fever and is included in Jones’ diagnostic criteria. Other electrocardiographic changes such as sinus tachycardia, bundle branch blocks, nonspecific ST-T wave changes, atrial and ventricular premature complexes have been reported with variable frequency. However, complete heart block is an exceptionally rare manifestation of acute rheumatic fever. We report a 15 years female who developed Complete heart Block during an episode of acute rheumatic carditis. The patient was successfully treated with conventional treatment and Temporary Pacemaker. DOI: http://dx.doi.org/10.3126/njh.v9i1.8351 Nepalese Heart Journal Vol.9(1) 2012 pp.56-58